2023
DOI: 10.1001/jamaoncol.2022.5874
|View full text |Cite
|
Sign up to set email alerts
|

Variability in COVID-19 Vaccine Response Among People With Cancer

Abstract: An estimated 17.6 million people have died of COVID-19 worldwide, with 18.9 million currently getting infected daily. 1 In this issue of JAMA Oncology, Lee and colleagues 2 show that people with cancer are vulnerable to SARS-CoV-2 breakthrough infection and COVID-19 hospitalization. Patients with hematologic cancers, with latestage cancer, or receiving systemic therapy had diminished vaccine antibody response, making them most vulnerable. This Editorial contextualizes the strengths and limitations of their res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…Moreover, they reported that patients with metastatic disease (stage IV) had lower anti-S antibody titers with a consequent higher risk of SARS-CoV-2 breakthrough infection. These results should encourage health professionals to create a more comprehensive strategy to support the pandemic-related needs of the frailest patients [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they reported that patients with metastatic disease (stage IV) had lower anti-S antibody titers with a consequent higher risk of SARS-CoV-2 breakthrough infection. These results should encourage health professionals to create a more comprehensive strategy to support the pandemic-related needs of the frailest patients [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reporting of cardiovascular complications stemming from COVID-19 in cancer patients has been limited. Many cancer patients are treated with immune checkpoint inhibitors (ICI), which have been known to be associated with myocarditis; however, this patient’s chemotherapy regimen did not include any ICIs [ 40 ]. This patient’s cancer treatment was held until she made a full recovery from COVID-19 and associated complications.…”
Section: Discussionmentioning
confidence: 99%
“…However, the subsequently confirmed metastatic breast cancer may have made her more vulnerable to developing this uniquely complicated case of COVID-19. It may also have made her response to the vaccine less robust [ 40 ]. It is also possible that the COVID-19 infection was simply coincident with the encephalitis and myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor We were impressed by the promising results from the national COVID-19 and cancer cross-sectional evaluation conducted by Lee et al, who reported an association of SARS-CoV-2 spike protein antibody vaccine response with infection severity among patients with cancer; these findings can help develop a health care strategy to protect vulnerable individuals . However, we still have a few concerns regarding this study.…”
mentioning
confidence: 94%